(untitled) (Research, Society and Development, 2020)
The objective of the study is to evaluate whether the Braden scale and its components have a discriminative capacity in the prognosis of developing pressure injuries, when applied in intensive care. Data were collected from 764 medical records of patients hospitalized between 2017 and 2018, 582 of which were considered valid. Association measures, hypothesis tests for differences between groups, bivariate correlation and logistic regression were performed. The mean age of the patients was 66.4 years and the average score obtained on the Braden scale was 12.57. There was a statistically significant difference in the development of pressure injuries between the high and low risk groups. When analyzing the components of the Braden scale, it was observed that ‘Sensory Perception’ and ‘Activity’ stand out as more associated with the development of pressure injury, but with significant correlation between them. ‘Moisture’ and ‘Nutrition’ had an insignificant performance in predicting pressure injuries. It is concluded that the Braden scale still has predictive capacity for pressure injuries in intensive care, despite the moderate performance, with compliance statistics of 0.710 in 2017 (95% confidence interval between 0.648 and 0.772) and 0.803 in 2018 ( between 0.755 and 0.852). The logistic regression model suggests that only the measurement of ’sensory perception’ has discriminatory performance equivalent to the Braden scale in intensive care in this sample.